Application of Response Surface Methodology for the Optimization of Copper Removal from Aqueous Solution by Activated Carbon Prepared Using Waste Polyurethane - Arslanoglu, Hasan; Orhan, Ramazan; Turan, M. Deniz (Taylor & Francis Inc, 2020)
Activated carbon was prepared from commercial polyurethane and polymer waste by chemical activation using zinc chloride. The prepared activated carbon was characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface analysis, elemental analysis, iodine number, surface functional groups, the pH of zero point charge (pH(zpc)), and the moisture and ash contents. The experimental parameters of pH, temperature, initial concentration, and adsorbent dosage were optimized for the removal of Cu (II) from aqueous solution. The adsorption mechanism for the removal of Cu(II) from aqueous solution by the activated carbon obtained from waste polyurethane by zinc chloride activation was characterized using pseudo-first order, pseudo-second order and intraparticle diffusion models, Fourier transform infrared spectroscopy, and SEM. These experiments were performed under the optimum conditions obtained using response surface methodology (RSM). The optimum conditions for pH, temperature, concentration, and adsorbent dosage were 5.7, 53 degrees C, 27 mg/L, and 4.2 g, respectively. The results were analyzed using isotherm and kinetic models. The highest monolayer adsorption capacity of Cu (II) ions onto the activated carbon was 31.95 mg/g. The pseudo-second order kinetic model was the ideal model. Approximately 80% of Cu (II) was removed from the solution.
Keywords: Activated carbon; adsorption; Box-Behnken; Cu(II) removal; polyurethane foam; response surface methodology